2011
DOI: 10.1186/1471-2458-11-893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lifestyle intervention in persons at risk for type 2 diabetes mellitus - results from a randomised, controlled trial

Abstract: BackgroundLifestyle change is probably the most important single action to prevent type 2 diabetes mellitus. The purpose of this study was to assess the effects of a low-intensity individual lifestyle intervention by a physician and compare this to the same physician intervention combined with an interdisciplinary, group-based approach in a real-life setting.MethodsThe "Finnish Diabetes Risk score" (FINDRISC) was used by GPs to identify individuals at high risk. A randomised, controlled design and an 18 month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 39 publications
2
62
0
Order By: Relevance
“…Based on normative data for the maximal aerobic capacity (V02 max) with respect to gender and age, the subjects were classified into six levels, i.e., very poor, poor, fair, good, excellent and superior aerobic capacity.14 A clinically signifi cant lifestyle change was characterized as a weight reduction of >5% and an improvement in the V02 max of >10% from baseline to follow-up. 12 The health-related quality of life (HRQOL) was assessed at baseline and follow-up using the Medical Outcomes Survey Short Form 36 (SF-36), and the re sults were used to calculate a physical component summary (PCS) and a mental component summary (MCS). The SF-36 is used internationally as a generic measure of self-reported HRQOL.…”
Section: Assessmentsmentioning
confidence: 99%
“…Based on normative data for the maximal aerobic capacity (V02 max) with respect to gender and age, the subjects were classified into six levels, i.e., very poor, poor, fair, good, excellent and superior aerobic capacity.14 A clinically signifi cant lifestyle change was characterized as a weight reduction of >5% and an improvement in the V02 max of >10% from baseline to follow-up. 12 The health-related quality of life (HRQOL) was assessed at baseline and follow-up using the Medical Outcomes Survey Short Form 36 (SF-36), and the re sults were used to calculate a physical component summary (PCS) and a mental component summary (MCS). The SF-36 is used internationally as a generic measure of self-reported HRQOL.…”
Section: Assessmentsmentioning
confidence: 99%
“…Improvements in body weight, diet and exercise capacity can easily be achieved with modest efforts 14. However, more intensive lifestyle interventions and, in particular, a weight loss of at least 5% maintained over a longer period of time had a more pronounced effect in European clinical trials 15,16.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons: Baseline to 12-month weight change data not reported: Costa et al, 78 Ma et al, 92 Nilsen et al, 83 Vermunt et al 91 Papers identified from reference lists (n = 20) a Boltri et al…”
Section: Scoring Of Intervention Contentmentioning
confidence: 99%
“…78 Three were excluded from all analyses as one study reported only 15-month data, 92 and two were excluded as they reported only 18-month data. 83,91 Two studies included in the meta-analysis had two intervention arms, 50,81 meaning that 27 study groups were analysed.…”
Section: Meta-analysismentioning
confidence: 99%